Optimal Controller Design for Automatic Generation Control Under Renewable Energy Disturbance - Attia M.A.; Mokhtar M.; Abdelaziz A.Y.; Sasis S.; Kumar S.; Saket R.K. (My University, 2025)
This paper presents a comparison between four types of optimization algorithms to design a suitable controller optimally for automatic generation control (AGC) under disturbance due to wind generator variation. To select the proper optimization technique, two case studies are considered. The first one is a single-area AGC without disruption due to wind generators, and the other research is carried out with the wind generator disturbance. In both cases, the system had a time delay and a small disruption at a specific time. In each case, four optimization techniques are carried out, gravitational search algorithm, genetic algorithm, the crow search algorithm, and the harmony search algorithm. The simulation results are performed using the MATLAB program. Also, a comparison between the techniques is carried out. Finally, the paper suggested a suitable method to design the controller of AGC according to the cases studied. © 2021, Springer Nature Singapore Pte Ltd.